Metabolism of oxysterols derived from nonenzymatic oxidation of 7-dehydrocholesterol in cells - Xu, Libin (The American Society for Biochemistry and Molecular Biology, 2013)
Recent studies suggest that 7-dehydrocholesterol (7-DHC)-derived oxysterols play important roles in the pathophysiology of Smith-Lemli-Opitz syndrome (SLOS), a metabolic disorder that is caused by defective 3β-hydroxysterol-Δ(7)-reductase (DHCR7). Although 14 oxysterols have been identified as the primary products of 7-DHC autoxidation in organic solution, the metabolic fate of these oxysterols in a biological environment has not yet been elucidated. Therefore, we incubated these primary 7-DHC oxysterols in control Neuro2a and control human fibroblast cells and identified metabolites of these oxysterols by HPLC-MS. We also incubated Dhcr7-deficient Neuro2a cells and fibroblasts from SLOS patients with isotopically labeled 7-DHC (d(7)-7-DHC). The observation of matching d(0)- and d(7) peaks in HPLC-MS confirmed the presence of true metabolites of 7-DHC after excluding the possibility of ex vivo oxidation. The metabolites of primary 7-DHC oxysterols were found to contribute to the majority of the metabolic profile of 7-DHC in cells. Furthermore, based on this new data, we identified three new 7-DHC-derived metabolites in the brain of Dhcr7-KO mice. Our studies suggest that 7-DHC peroxidation is a major source of oxysterols observed in cells and in vivo and that the stable metabolites of primary 7-DHC oxysterols can be used as markers of 7-DHC peroxidation in these biological systems.